Pengaruh ROE dan DOL Terhadap Struktur Modal Era Digitalisasi Sektor Consumer Non-Cyclicals - Marcella Agustin; Ratna Juwita (Universitas Multi Data Palembang, 2026)
The purpose of this study is to determine the effect of Return on Equity (ROE) and Degree of Operating Leverage (DOL) on the Capital Structure of companies in the digitalization era of the Consumer Non-Cyclicals sector. Quantitative methods were used in this study with a research population of 131 companies. The research sample consisted of 77 companies selected using a purposive sampling method with a total sample of 462 samples. The results of the study indicate that partially Return on Equity (ROE) has a significant positive effect and Degree of Operating Leverage (DOL) has a significant negative effect on Capital Structure. Simultaneously, Return on Equity (ROE) and Degree of Operating Leverage (DOL) have a significant positive effect on Capital Structure.